Preliminary evaluation of tropical forage legumes during the dry season - Souto, Sebastião Manhães; Lucas, Enésio Delgado de (Pesquisa Agropecuaria Brasileira, 2014)
An empirical evaluation based on vegetative character (amount of green leaves/plot) was made on a group of five forage legume species, including 71 cultivars, during the dry season of the year (April through September). For this evaluation, initiated in 1963 and ended in 1970, notes were give to each cultivar according to a scale of points varying from 1 to 4. Phaseolus atropurpureus D.C., Glycine javanica L. and Stylosanthes gracilis H.B.K. were the species which presented the largest number of cultivars with an average above 2.5.